Does Nipple-Ward Positive Margin Contribute to a Higher Rate of Re-Excision Procedures After a Lumpectomy with Pathology-Confirmed Positive Margins? A Retrospective Study - Bhimani F; Lin S; McEvoy M; Cavalli A; Obaid L; Chen Y; Gupta A; Pastoriza J; Shihabi A; Feldman S (Breast Cancer: Targets and Therapy, 2024)
Fardeen Bhimani,1,* Sophie Lin,1,* Maureen McEvoy,1,2 Arianna Cavalli,2 Liane Obaid,2 Yu Chen,1 Anjuli Gupta,1,2 Jessica Pastoriza,1,2 Areej Shihabi,1 Sheldon Feldman1,2 1Breast Surgery Division, Department of Surgery, Montefiore Medical Center, Montefiore Einstein Center for Cancer Care, Bronx, New York, USA; 2Albert Einstein College of Medicine, Bronx, New York, USA*These authors contributed equally to this workCorrespondence: Sheldon Feldman, Department of Surgery, Division of Breast Surgery, Montefiore Medical Center, 1250 Waters Place, 7th Floor, Hutch Tower 1, Bronx, NY, USA, Email sfeldman@montefiore.orgBackground: Positive margins on lumpectomy specimens are associated with a twofold increased risk of local breast tumor recurrence. Prior literature has demonstrated various techniques and modalities for assessing margin status to reduce re-excision rates. However, there is paucity of literature analyzing which margin contributes to the highest re-excision rates. Therefore, the primary aim of the study was to investigate whether the nipple-ward margins resulted in a higher rate of re-excision in our patient population.Methods:  A retrospective chart review was performed on patients who had re-excision surgery. Nipple-ward margin was identified by correlating radiological and pathological reports. A cut-off of more than 25% was used to demonstrate correlation between nipple-ward margin and re-excision rate.Results: A total of 98 patients’ data were analyzed, with 41 (41.8%), 14 (14.3%), 5 (5.1%), and 38 (38.8%) diagnosed with DCIS, IDC, ILC, and mixed pathology on their margins, respectively. Overall, 48% (n=47) of the positive margins were nipple-ward, with 44.7% (n=21) reporting DCIS. Upon stratification, 45 (45.9%) cases were single-margin positive, with 26 (57.8%) being nipple-ward. Furthermore, the remaining 53 (54.1%) patients had multiple positive margins, with 21 (39.6.7%) nipple-ward cases.Conclusion: Positive nipple-ward margins significantly contribute to a higher re-excision rate p < 0.001; 48% of re-excision surgeries had positive nipple-ward margins, and 57.8% of positive single-margin cases were nipple-ward. Taking an additional shave during initial lumpectomy decreases re-excision rates. However, planning a lumpectomy procedure with a more elliptical rather than a spherical resection with additional cavity shave (ie, larger volume) in the nipple-ward direction and minimizing the remaining cavity shaves so the total volume resected remains unchanged. Nevertheless, future studies with larger sample sizes are required to bolster our findings.Keywords: nipple-ward, breast cancer, re-excision, nipple-ward positive breast cancer, Shave trial, positive margins